Relational Embeddedness and Socially Motivated Case Screening in the Practice of Law in Rural China. Issue 4 (7th November 2016) - Li, Ke
Abstract : Based on an ethnographic study conducted in rural China, this article demonstrates that relational embeddedness —that is, concrete and durable relationships among law practitioners, clients, adversaries, and the surrounding communities—holds the key to our understandings of the legal profession's case screening. Over the past decade, legal services in rural China have been commodified significantly. Despite that, relationships with extended families, community members, and local political elites have continued to shape law practitioners' professional decision‐making. By carefully scrutinizing multiplex relationships involved in legal services, law practitioners seek to meet the practical needs of their personal life, and more importantly, to uphold moral obligations derived from communal life. Seen in this light, the practice of law is an integral part of a moral economy in the countryside. Rather than giving rise to a more progressive form of services, the legal profession's participation in this moral economy often reinforces existing power structures in Chinese society. By introducing the concept of relational embeddedness into sociolegal research, this study unpacks the complex consequences of the recent legal reforms in China; it also enriches our theoretical understandings of related concepts, such as social capital, networking, and guanxi in the practice of law.